2019
DOI: 10.1111/jgh.14942
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Helicobacter pylori eradication therapy in Myanmar; a randomized clinical trial of efficacy and tolerability

Abstract: Background and Aim There is little published research to examine the best approach to the management of Helicobacter pylori in Myanmar. This study aimed to determine the relative efficacy and tolerability of sequential eradication therapy compared to Myanmar's current recommendation of a concomitant four drug regimen. Methods Patients were screened for H. pylori using monoclonal Stool Antigen Testing (SAT). Those testing positive were randomized 1:1 to receive receive Myanmar's first‐line regimen of 14 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Via a full-test review, 12 studies were obsolete for specific reasons. Finally, only 24 studies [10–33] were incorporated. Additional details about the study selection could be found in .…”
Section: Resultsmentioning
confidence: 99%
“…Via a full-test review, 12 studies were obsolete for specific reasons. Finally, only 24 studies [10–33] were incorporated. Additional details about the study selection could be found in .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that once patients in Myanmar are able to access ART they usually do well. This may be explained by the fact that all HIV care in Myanmar is free of charge, that there is increasing access to contemporary ART (over 80% of this cohort received a dolutegravir-based regimen) and that medication adherence is generally excellent [ 3 , 19 ]. The Global Fund to fight AIDS, Tuberculosis and Malaria provides funding for peer support workers who support HIV care, provide counselling and psychosocial support and who play a crucial role in ensuring retention in care [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to PP analysis, their eradication rates were 95% and 93%, respectively, and according to ITT analysis results, they were 79% and 82.5%, respectively. 27 Similarly, in Korea, a multicenter RCT involving 1141 people showed that in first-line treatment, the eradication rate of the 10-day CT regimen was significantly higher than that of the 7-day triple therapy regimen (ITT, 81.2% versus 63.9%; PP, 90.6% versus 71.4%); the eradication rate of the 10-day ST regimen was also better than that of the 7-day triple therapy regimen (ITT, 76.3% versus 63.9%; PP, 85.0% versus 71.4%), and there was no significant difference in adverse reactions among the three regimens. 28 In Egypt, a prospective study not only compared the efficacy between ST and standard triple treatment but also estimated the optimal duration of ST. Studies have shown that ST is superior to triple therapy, especially when ST lasts for 14 days (96.7% versus 90.7% versus 63.3%).…”
Section: Empirical Treatmentmentioning
confidence: 99%